Scaling climate information services and climate smart agriculture through bundled business models - Kagabo, Desire M.; Byandaga, Livingstone; Gatsinzi, Patrick; Mvuyibwami, Patrick; Munyangeri, Yvonne U.; Ntwari, Nasson; Ouedraogo, Mathieu (Elsevier, 2025)
There is a general agreement among scholars that bundling Climate Information Services (CIS), Climate Smart Agriculture (CSA), and other agricultural products and services can positively impact agriculture. However, many questions still need to be answered regarding how the bundling can be achieved through scalable and farmer-centric CIS-CSA bundled business models. This study narrowed the knowledge gap by revealing 1) how CIS, CSA, and other agricultural products and services may be bundled to support sustainable agriculture, 2) what types of CIS-CSA bundled business models are successfully reaching and benefiting farmers and entrepreneurs, and 3) proposing an evaluation framework for assessing CIS-CSA bundled business models ready for scaling. Drawing on the synthesis analysis of available relevant publications, we devised a 1–5 scale evaluation framework based on nine scaling readiness indicators—technology, impact, bundling, infrastructure, relevance, evidence, barriers, sustainability, and value addition—to assign scalability scores to 29 business cases with bundled CIS-CSA products and services across Africa and Asia. Eleven CIS-CSA bundled business models with publicly available quantitative scaling readiness data (financial capacity, the number of customers, customer categories, and the number of beneficiaries) were used to quantitatively model how different CIS-CSA products and services bundling strategies, the revenue stream structure of a CIS-CSA business, and the structure of a CIS-CSA business’s stakeholder network (the diversity of its stakeholders) affect its scaling readiness. Based on the scaling readiness evaluation framework, of the 29 identified CIS-CSA bundled business cases, 12 were ready for scaling. The quantitative analysis revealed that the type of a CIS-CSA model significantly determines its scalability— for example, a government-to-donor-to-business-to-consumer (G2D2B2C) CIS-CSA bundled business model would have 10 million USD more invested capital than a government-to-business-to-consumer (G2B2C) bundled business model type. Additionally, the G2D2B2C bundled business model type would serve 5 million farmers and three customer categories and gain ten partners more than the G2B2C. The finding also suggests that multi-stakeholder CIS-CSA business models, which provide a more diverse package of CIS-CSA products and services and have many revenue sources, have the potential to benefit all categories of farmers and entrepreneurs. This study reveals a reason for optimism about the future of agriculture; it suggests that scalable bundled CIS-CSA products and services can contribute significantly to attaining climate resilience and food security.